2010
DOI: 10.1074/jbc.m110.168385
|View full text |Cite
|
Sign up to set email alerts
|

Three Enzymatic Steps Required for the Galactosamine Incorporation into Core Lipopolysaccharide

Abstract: The core lipopolysaccharides (LPS) of Proteus mirabilis as well as those of Klebsiella pneumoniae and Serratia marcescens are characterized by the presence of a hexosamine-galacturonic acid disaccharide (␣HexN-(1,4)-␣GalA) attached by an ␣1,3 linkage to L-glycero-D-manno-heptopyranose II (L-glycero-␣-D-manno-heptosepyranose II). In K. pneumoniae, S. marcescens, and some P. mirabilis strains, HexN is D-glucosamine, whereas in other P. mirabilis strains, it corresponds to D-galactosamine. Previously, we have sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…The waa gene cluster (homologous to rfa in E. coli) encompasses genes that synthesize and modify the hexose region of the lipopolysaccharide (LPS) core in stepwise fashion (26,27). WaaC is involved in the addition of HepI to KdoI of the inner core and WaaF in the addition of HepII to HepI, and WaaQ appears to be involved in the addition of HepIII to the outer core (28,29). All three are presumed heptosyltransferases, and null mutations in cognate gene rfaC or rfaF yield deep, rough mutants in E. coli and S. Typhimurium (27,30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The waa gene cluster (homologous to rfa in E. coli) encompasses genes that synthesize and modify the hexose region of the lipopolysaccharide (LPS) core in stepwise fashion (26,27). WaaC is involved in the addition of HepI to KdoI of the inner core and WaaF in the addition of HepII to HepI, and WaaQ appears to be involved in the addition of HepIII to the outer core (28,29). All three are presumed heptosyltransferases, and null mutations in cognate gene rfaC or rfaF yield deep, rough mutants in E. coli and S. Typhimurium (27,30).…”
Section: Resultsmentioning
confidence: 99%
“…The gene wabH, an rfaG homologue, constitutes part of the same locus. WabH catalyzes the transfer of GlcNAc from UDP-GlcNAc to the outer core, and wabH mutants also produce truncated LPS (29,31).…”
Section: Resultsmentioning
confidence: 99%
“…An alignment between these two glycosyltransferases (WaaO, Q8KMW9; WaaI, Q9ZIT4) revealed that they share 51 and 80% amino acid residue identity and similarity, respectively. These levels of identity/similarity are similar to the ones shared by the P. mirabilis N-acetylglucosaminyl (WabH R110 ) and N-acetylgalactosaminyl (WabP 50/57 ) transferases (42). P. shigelloides WapE is a UDP-galactose transferase ␤-(1¡4) to L-HepI instead of the UDP-glucose transferase ␤-(1¡4) to LHepI characteristic of the Klebsiella-Serratia-Proteus group.…”
Section: Discussionmentioning
confidence: 56%
“…We previously showed that the incorporation of GlcN in the LPS core requires two distinct enzymatic steps due to the lack of UDP-GlcN in prokaryotes (39,42). First, one enzyme catalyzes the incorporation of GlcNAc from UDP-GlcNAc to outer-core LPS, and then a second enzyme catalyzes the deacetylation of the core LPS containing the GlcNAc residue.…”
Section: Discussionmentioning
confidence: 99%
“…Some P. mirabilis core-OS structures contain unusual residues such as quinovosamine, an open-chain form of N -acetyl-galatosamine, or amide linked amino acids. Recently, most of the genes involved in the biosynthesis of the sugar backbone of the core LPS from several P. mirabilis strains have been identified and characterized [ 10 , 11 ]. Little is known about the role of the non-sugar charged residues or groups in the core OS.…”
Section: Introductionmentioning
confidence: 99%